HUBUNGAN ANTARA UMUR IBU DENGAN KLASIFIKASI LABIOSCHISIS DI RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO - Artathi Eka Suryandari (Universitas Muhammadiyah Kudus, 2017)
Labio palatoshcisis cleft lip or palate is a congenital defect such as a crack in the upper lip, gums, jaw and palate. Congenital abnormalities is ranked third highest based on a survey conducted in 13 major hospitals in Indonesia. The purpose of this study was to analyze the relationship between maternal age with labioschisis classification. This study used cross sectional retrospective design, data extracted from medical records during the period January , 2010 to December, 2016. Total sample of 42 respondents, the data were analyzed using chi squaretest with significance level ρ value of 0.005. The results showed that most respondents had labioschisis at 57%, while 43% of respondents experienced labiopalatoschisis and labiognatopalatoschisis. The lives of most mothers with children experiencing labioschisis is 20-35 years old ie 67%. There was no relationship between the mother's age with classification labioschisis (ρvalue 0.186).